PENERAPAN ALGORITMA LEVENSHTEIN DISTANCE UNTUK PENCARIAN PADA SISTEM INFORMASI PERPUSTAKAAN FAKULTAS KEDOKTERAN UNIVERSITAS PALANGKA RAYA - Widiatry, Widiatry; Sari, Nova Noor Kamala; Pranatawijaya, Viktor Handrianus; Adidyana Anugrah Putra, Putu Bagus (STMIK Palangkaraya, 2019)
The library of Faculty of Medicine of University of Palangka Raya is one of the libraries that regulates its management conventionally, and has not utilized computer technology optimally. So that, the library needs to improve its performance over the time, perticularly in delivering information on books or in terms of circulation services of book borrowing and returning transactions. The methodology used in making this information system is method of modified Waterfall software. This method consists of four stages; (1) Analysis; (2) Design; (3) Implementation; (4) Testing. Errors in typing the words searched for by the users could cause the searching for information cannot be found. Thus, levenshtein distance algorithm would be able to display autocorrect or provide the word suggestions to improve the title of the book that had the closest distance value to the word typed. Based on the results of the levenshtein distance algorithm calculation for the single target book title search, it has an accuracy of 75%; for the multi target book title with 2 words, it has an accuracy of 64.29%; for the multi target book title with 3 words, it has an accuracy of 66.75%, and; for the multi target book title with 4 words has an accuracy of 70.83%.